Komik Online “Ngopi, Yuk!”: Kajian Praanggapan dalam Perspektif Pragmatik - Bambang Eko Hari Cahyono; Arifah Putri Nur Nadila (Ranah: Jurnal Kajian Bahasa, 2024)
The scope of pragmatic studies consists of 3 components, namely presupposition, conversational implicature, and entailment. One of the pragmatic studies that examines the meaning of assumptions or assumptions in speaking is presupposition. This study aims to describe and explain the dominant forms of presupposition in the online comic "Ngopi, Yuk!" episodes 929—1073. The type of research used was qualitative descriptive research. Data collection techniques used were listening and note-taking techniques. Data analysis used was an interactive analysis model which was carried out at the time or during and after data collection. Data analysis was carried out through 3 simultaneous activity flows, namely data reduction, data presentation, and drawing conclusions/verification. The results of the study shows that 3 most dominant forms of presupposition are found, namely 33 existential presuppositions, 18 structural presuppositions, and 27 factive presuppositions. Existential  presuppositions are characterized by the existence of a place, anentity, a person, time, words and phrases that indicate a person's atmosphere and condition. Structural presuppositions are marked by interrogative sentences or question words, while factive presuppositions are indicated by the use of verbs, verb phrases, adjectives, and adjective phrases. AbstrakPenelitian ini bertujuan untuk mendeskripsikan dan menjelaskan bentuk-bentuk praanggapan yang dominan dalam komik online “Ngopi, Yuk!” episode 929—1073. Jenis penelitian yang digunakan adalah penelitian deskriptif kualitatif. Teknik pengumpulan data menggunakan teknik simak dan catat. Analisis data menggunakan model analisis interaktif yang dilaksanakan pada saat atau selama berlangsungnya pengumpulan data dan setelah pengumpulan data. Analisis data dilakukan melalui 3 alur kegiatan yang berlangsung secara bersamaan, yaitu reduksi data, penyajian data, dan penarikan simpulan/verifikasi. Hasil penelitian menunjukkan bahwa ditemukan 3 bentuk praanggapan yang paling dominan, yaitu praanggapan eksistensial sebanyak 33, praanggapan struktural sebanyak 18, dan praanggapan faktif sebanyak 27. Praanggapan eksistensial ditandai dengan adanya eksistensi tempat, entitas sesuatu, orang, waktu, kata dan frasa yang menunjukkan suasana serta keadaan seseorang. Praanggapan struktural ditandai dengan kalimat interogatif atau kata tanya, sedangkan bentuk praanggapan faktif ditunjukkan dengan penggunaan verba dan frasa verba dan adjektiva dan frasa adjektiva.